End-User Development 9th International Symposium, IS-EUD 2023, Cagliari, Italy, June 6-8, 2023, Proceedings - Spano, Lucio Davide; Schmidt, Albrecht; Santoro, Carmen; Stumpf, Simone (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 9th International Symposium on End-User Development, IS-EUD 2023, held in Cagliari, Italy, during June 6-8, 2023. The 17 full papers and 2 (keynote extended abstracts) included in this book were carefully reviewed and selected from 26 submissions. They were organized in topical sections as follows: Artificial Intelligence for End-Users; Internet of Things for End-Users; Privacy; Security and Society; Supporting End-User Development.
Artificial Intelligence for End-Users -- Adaptive and Adaptable Systems: Differentiating and Integrating AI and EUD -- End-User Development for Artificial Intelligence: A Systematic Literature Review -- Human-AI Co-Creation: Evaluating the Impact of Large-scale Text-to- Image Generative Models on the Creative Process -- Leveraging Large Language Models for End User Website Generation -- Internet of Things for End-Users -- Defining Trigger-Action Rules via Voice: a Novel Approach for End-User Development in the IoT -- Language and Temporal Aspects: A Qualitative Study on Trigger Interpretation in Trigger-Action Rules -- Understanding Concepts, Methods and Tools for EndUser Control of Automations in Ecosystems of Smart Objects and Services -- Understanding User Needs in Smart Homes and How to Fulfil Them -- Privacy, Security and Society -- Democratizing Cybersecurity in Smart Environments: Investigating the Mental Models of Novices and Experts -- On the User Perception of Security Risks of Trigger-Action Rules: A User Study -- ConnectivityControl: Providing Smart Home Users with Real Privacy Configuration Options -- Designing for a Sustainable Digital Transformation: The DEA Methodology -- Supporting End-User Development -- Exploring visual languages for prototyping interactive behaviors for Tangible Virtual Reality -- How End Users Develop Point-and-Click Games -- Programming with Minecraft Bedrock Up: Modeling, Coding, and Computational Concepts -- Challenges of Enabling End-Users to Develop Systems with AI -- EUD Strategy in the Education Field for Supporting Teachers in Creating Digital Courses.
Keywords: Software engineering; Software Engineering